Shoulder Tendon Adaptations Following a Graded Exercise Test to Exhaustion in Highly Trained Wheelchair Rugby Athletes With Different Impairments - Bossuyt, Fransiska Marie; Mason, Barry S.; Briley, Simon; O'Brien, Thomas J.; Boninger, Michael L.; Arnet, Ursina; Goosey-Tolfrey, Victoria Louise (Frontiers in Rehabilitation Sciences, 2022)
Objective: This study aimed to identify acute changes in biceps and supraspinatus tendon characteristics before and after a graded exercise test to exhaustion (GXT) in highly trained wheelchair rugby (WR) athletes. A secondary aspect was to define chronic tendon adaptations related to the impairment of the athlete and the occupation of the tendon within the subacromial space (occupation ratio). Methods: Twelve WR athletes with different impairments (age = 32 ± 6 years; body mass = 67.2 ± 11.2 kg; 9.0 ± 3.6 years competing) volunteered for this study. Performance Corrected Wheelchair Users Shoulder Pain Index was used to quantify shoulder pain. Quantitative Ultrasound Protocols were used to define supraspinatus and biceps tendon thickness, echogenicity, and echogenicity ratio of both dominant and non-dominant shoulder before and after the GXT including 22 ± 3.1 min submaximal propulsion and 10.2 ± 1.7 min maximal propulsion on a treadmill. Furthermore, the acromio-humeral distance defined from ultrasound images was used to calculate the occupation ratios. Results: A mixed-effect multilevel analysis that included shoulder as grouping variable, demonstrated a significant reduction in the echogenicity of the biceps following GXT whilst controlling for impairment (spinal cord injury (SCI) and non-SCI) and the occupation ratio (β = -9.01, SEβ = 2.72, p = 0.001, 95% CI = [-14.34;-3.68]). This points towards fluid inflow into the tendon that may be related to overload and acute inflammation. In addition, persons with a SCI (n = 8) had a thicker supraspinatus tendon in comparison to persons with non-SCI (n = 3) which may be related to chronic tendon adaptations (β = -0.53mm, SEβ = 0.26, p = 0.038, 95% CI = [-1.04;-0.03]). Finally, a greater occupation ratio was associated with signs of tendinopathy (i.e., greater biceps and supraspinatus tendon thickness, and lower supraspinatus echogenicity and echogenicity ratio). Conclusion: Acute biceps tendon adaptations in response to the GXT in highly trained WR athletes were evident with chronic adaptations in the supraspinatus tendon being related to the impairment of the athlete. Ultrasound can be used to monitor tendon adaptations in WR athletes for medical diagnosis to assist the scheduling and type of training.